Volume 1B: Combustion, Fuels and Emissions 2013
DOI: 10.1115/gt2013-96000
|View full text |Cite
|
Sign up to set email alerts
|

High Fidelity Simulation of the Spray Generated by a Realistic Swirling Flow Injector

Abstract: Practical aero-engine fuel injection systems are highly complicated, combining complex fuel atomizer and air swirling elements to achieve good fuel-air mixing as well as long residence time in order to enhance both combustion efficiency and stability. While detailed understanding of the multiphase flow processes occurring in a realistic injector has been limited due to the complex geometries and the challenges in near-field measurements, high fidelity, first principles simulation offers, for the first time, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…An estimate of the Kolmogorov scale in the crossflow is given by η ∼ DRe − 3 4 g = 1.06µm. Though the smallest grid we use is ≈ 23η and doesn't capture the detailed flow, we believe it is good enough to capture the breakup dynamics of the droplets produced during breakup and is more resolved than most of the previous studies (for example, Li et al (2014) used a grid ≈ 130 times larger than η). Figure 2 shows the adaptively refined grid used in the simulations on a plane containing the annular axis and the injection point.…”
Section: Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…An estimate of the Kolmogorov scale in the crossflow is given by η ∼ DRe − 3 4 g = 1.06µm. Though the smallest grid we use is ≈ 23η and doesn't capture the detailed flow, we believe it is good enough to capture the breakup dynamics of the droplets produced during breakup and is more resolved than most of the previous studies (for example, Li et al (2014) used a grid ≈ 130 times larger than η). Figure 2 shows the adaptively refined grid used in the simulations on a plane containing the annular axis and the injection point.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Thus a numerical investigation can complement the experimental observations to attain a better understanding of the involved physics. Due to the constraints on experimental conditions and choice of the working liquid, previous experimental studies on LJICF were mostly limited to high density ratio flows (Vich, 1997;Mazallon et al, 1999;Wu et al, 1997), whereas computational studies have been performed for both low and high density ratios (Aalburg et al, 2005;Elshamy and Jeng, 2005;Elshamy, 2007;Hermann, 2010Hermann, , 2011Behzad et al, 2015Behzad et al, , 2016Xiao et al, 2013;Li et al, 2014). A comparative study for density ratios of 10 and 100 by (Hermann, 2011) showed that with an increase in the density ratio: (a) penetration of the liquid jet increases, (b) bending of the liquid jet reduces, (c) spread of the spray in the transverse direction increases and (d) wavelength of the traveling wave on the jet and the surface wave seen on the jet decreases, thus producing smaller droplets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation